Integration and Growth in a Globalized World Economy. (International Monetary Fund, 1999)
This paper presents four commentaries by an IMF Deputy Managing Director on integration and growth in a globalized world economy. Globalized and integrated financial markets are the norm, complete with their tremendous opportunities-the chance to quicken the pace of investment, job creation, and growth-and, some inevitable risks. The paper also highlights that sound macroeconomic policies must be a top priority, and that these policies must be supported by transparency and accountability. Policies at the country and global level must be mutually reinforcing; industrial countries meeting the more outward-oriented policies of developing countries with greater openness around the world. It is recommended that the IMF agenda must include adopting bold structural reforms and building a social consensus for reform through economic security, good governance, and a better dialogue with civil society in Africa. In the Berlin address, it is suggested that development rests on three pillars: good economic policy, a favorable legal and political environment, and attention to equitable social development.